Android-Based Internal Quality Audit Application Development at the Faculty of Educational Sciences State University Surabaya - Mohammad Shahidul Haq; Erny Roesminingsih; Nur Aini Dwi Setyowati; Firman Ashadi; Denok Dwi Anggraini (Jurnal Penelitian Pendidikan IPA, 2023)
Internal quality audit is considered an important tool to control the governance and operations of an organization. As an independent and objective assurance and advisory function, internal quality audit is designed to increase value through audits of internal control systems, risk management, and governance processes. Awareness of the importance of internal quality audit and also the fact that its effectiveness can be measured is what led the author to conduct research and development of an Android-Based Internal Quality Audit Application, which aims to facilitate the Internal Quality Audit process at the Faculty of Education, State University of Surabaya. The development of the Internal Quality Audit Instrument is carried out by adapting the ADDIE research and development model. The results of the study showed that each category tested got the results, namely: 90% for the functional category; 90% for the design category; 89% for the ease-of-use category; 87% for the suitability need category. The results of the study also explained that the Android-Based Internal Quality Audit Application, Faculty of Education, State University of Surabaya has been effective in each category and is good to be implemented.